2000
DOI: 10.1103/physrevlett.85.3033
|View full text |Cite
|
Sign up to set email alerts
|

Aging in a Relaxor Ferroelectric: Scaling and Memory Effects

Abstract: A crossover as a function of temperature is found in the zero-field aging properties of the relaxor ferroelectric Pb(Mg(1/3)Nb(2/3))O3. Below a temperature near which nonlinear susceptibility has indicated a suspected phase transition, the time-frequency dependence shows simple scale-independent behavior resembling that for spin glasses. As in spin glasses, high temperature aging is stable as further aging occurs at lower temperature, but not vice versa, indicating hierarchical state arrangement. A more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 30 publications
4
48
0
1
Order By: Relevance
“…The same tendency is observed for the sample quenched from other temperatures between T m and T f , which is consistent with the previously known single-stage and multiple-stage aging processes in the literature. 8,10,12,14,15 When quenched from 300 C, which is much higher than T m (92 C at 1 kHz), the total permittivity increases considerably without any splitting in the permittivity, as seen in Figs. 1(a) and 1(b) (q300).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The same tendency is observed for the sample quenched from other temperatures between T m and T f , which is consistent with the previously known single-stage and multiple-stage aging processes in the literature. 8,10,12,14,15 When quenched from 300 C, which is much higher than T m (92 C at 1 kHz), the total permittivity increases considerably without any splitting in the permittivity, as seen in Figs. 1(a) and 1(b) (q300).…”
mentioning
confidence: 58%
“…8 Apart from the practical implications, 9 the aging behavior of relaxor ferroelectrics is of special interest because it has been known to be directly related to the physics of the freezing of PNRs at low temperatures. 10 Given this, Pan et al 11 proposed that a "hardening" of inhomogeneously distributed long-range ordered regions is responsible for the aging in PMN-PT, while Colla et al 12 considered spin-glass and thermal chaos effect as the origin of aging. However, it was later demonstrated that the aging effect is not solely confined to the temperatures near the freezing temperature that is known to match the depolarization temperature, 6,13 but is also notable even above the maximum dielectric temperatures of the usual frequency range of kilohertz.…”
mentioning
confidence: 99%
“…We also found that NMTO shows the ME version of 'memory effect', which is common in glassy systems [18][19][20][21] . First, we took P [1][2][3][4][5][6][7][8][9][10] by a usual measurement process: Fig.…”
Section: Me Memory Effectmentioning
confidence: 82%
“…[12][13][14]16,17,22 Aging at E ¼ 0, with no evidence that any FE domains are present above the scale of the nanodomains, leads to dramatic slowing of these kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…The glassy relaxor order, which does not entirely go away when the FE state is formed, is an obvious possible contributor to these slow kinetics. A variety of experiments on the effects of aging on the susceptibility [12][13][14]16,17 show behavior characteristic of spinglasses, including the persistence of multiple "holes" in the susceptibility vs. T after aging at several T's, unlike the effects of simple domain growth. 18 We show here that the kinetics of the formation and melting of FE states are indeed very sensitive to the history of the sample in the glassy, non-FE regime, even when the resulting FE states have virtually identical polarizations.…”
Section: Introductionmentioning
confidence: 99%